Parameter optimization and test of harvesting device for digging and pulling green onions based on discrete element analysis - Wang, Wenlong; Zhang, Dekang; Wang, Xin; Wang, Fangyan (International Journal of Agricultural and Biological Engineering, 2025)
In green onion harvesting, the problems of easy dumping and low rate of clean digging can be encountered. In this paper, a kind of harvesting device for digging and pulling green onions, referred to simply as "the device", was designed. The device mainly consists of a digging shovel, screen bars, clamping conveyor belt, etc. This paper focuses on the analysis of the model forces of green onions and soil in the two states of the onion digging process without dumping and clamping. The key factors affecting the model state of onions and soil were identified as: screen bar length l2, screen bar inclination angle β, and pulling point position x. Based on the discrete element simulation technology of EDEM, the mechanism-crop-soil model was established, and a single-factor simulation test was conducted to determine the range of values for each factor. Taking the advantages of field test and three-factor five-level orthogonal experimental design, the parameter combinations of green onion harvesting operation evaluation indices were optimized, including a pulling point position of 166 mm, screen bar length of 242 mm, and screen bar inclination angle of 14°. As the results of the field test show, the harvester operation was stable without congestion or damage, the harvesting effect of green onions was improved, and the clean digging rate reached 100%, which meets the agronomic requirements for onion harvesting and the expectations of users. Keywords: green onions, digging and pulling, clamping, EDEM, test design DOI: 10.25165/j.ijabe.20251802.9513 Citation: Wang W L, Zhang D K, Wang X, Wang F Y. Parameter optimization and test of harvesting device for digging and pulling green onions based on discrete element analysis. Int J Agric & Biol Eng, 2025; 18(1): 165–172.